Il ruolo educativo e generativo dell’anziano in famiglia nell’epoca della globalizzazione - Bossio, Francesco (Rivista Italiana di Educazione Familiare, 2016)
The market economy is playing an increasingly pervasive role in our hyper-technological and globalized society, becoming, at the same time, an existential paradigm which finds its fulfillment in the relentless pursuit of individual happiness often followed through the continuous research of material assets. In this contest the elderly man is usually perceived as an anachronistic subject that is far from fashions and trends of the complex society; for this reason he is considered a deviant or a stranger in relation to the chaotic social changes. Starting from this premises, this paper analyzes, inside the complex social context, the role of the elderly man as a witness of experience and a mentor of education in the family. The old man, avoiding the collective rituals of everyday life, is emancipated from the inauthenticity of the society to ascend in the direction of the original dimension of the self. Within the family context, the old man, grandfather, can assume the role of primary educator; he can be a model of humanity and coherence able of cultivating and caring for the young.